Challenges of the epidemiological and economic burdens associated with hypertension in middle income countries: evidence from Mexico. (December 2015) - Arredondo, Armando; Cuadra, Silvia; Duarte, Maria
Abstract Background In order to identify the challenges resulting from hypertension in a middle income country, this study has developed probabilistic models to determine the epidemiological and economic burden of hypertension in Mexico. Methods Considering a population base of 654, 701 reported cases of adults with hypertension, we conducted a longitudinal analyses in order to identify the challenges of epidemiological changes and health care costs for hypertension in the Mexican health system. The cost-evaluation method used was based on the instrumentation technique. To estimate the epidemiological changes for 2015–2017, probabilistic models were constructed according to the Box-Jenkins technique. Results Regarding changes in expected cases for 2015 vs. 2017, an increase of 12 % is expected (p  < 0.001). Comparing the economic impact in 2015 versus 2017 (p  < 0.001), there is a 23 % increase in financial requirements. The total amount for hypertension in 2016 (US dollars) will be $6306, 685, 320 Of these, $ 2990, 109, 035 will be as direct costs and $ 3316, 576, 285 as indirect costs. Conclusions If the risk factors and care models remain as they are currently in the health system, the financial consequences will have a major impact on the out-of-pocket users, following in order of importance, on social security providers and on public assistance providers.